2022
DOI: 10.3390/nu15010019
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Promotes Bone Marrow Microenvironment by Inhibiting Adipsin in Diet-Induced Male Obese Mice

Abstract: Obesity is a growing global epidemic linked to many diseases, including diabetes, cardiovascular diseases, and musculoskeletal disorders. Exercise can improve bone density and decrease excess bone marrow adipose tissue (BMAT) in obese individuals. However, the mechanism of exercise regulating bone marrow microenvironment remains unclear. This study examines how exercise induces bone marrow remodeling in diet-induced obesity. We employed unbiased RNA-Seq to investigate the effect of exercise on the bone marrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The ECM-receptor interaction pathway plays an important role in bone homeostasis through 3 ECM proteins, namely laminin, fibronectin, and collagen. Studies have shown that ECM-receptor interaction could regulate bone metabolism by influencing the function of osteoclasts, and thus affect the bone microenvironment ( Shi et al, 2022 ). The mTOR signaling pathway plays a role in bone size and quality control, regulating bone length and width primarily by coordinating MSC proliferation and differentiation, and increasing bone mineral content by inhibiting osteoclast activity and differentiation ( Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ECM-receptor interaction pathway plays an important role in bone homeostasis through 3 ECM proteins, namely laminin, fibronectin, and collagen. Studies have shown that ECM-receptor interaction could regulate bone metabolism by influencing the function of osteoclasts, and thus affect the bone microenvironment ( Shi et al, 2022 ). The mTOR signaling pathway plays a role in bone size and quality control, regulating bone length and width primarily by coordinating MSC proliferation and differentiation, and increasing bone mineral content by inhibiting osteoclast activity and differentiation ( Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This immunosuppressive effect could theoretically allow for the proliferation of pre-leukemic cells. PA impacts bone turnover and the bone marrow microenvironment [182]. Alterations in this microenvironment due to intense exercise might influence hematopoietic stem cells and potentially lead to leukemogenesis.…”
Section: Obesity and Adipositymentioning
confidence: 99%
“…Of note, while the capacity of exercise to reduce adipose tissue deposits in humans is well known ( 130 ), a murine study showed that aerobic exercise can also decrease dietary-induced BM adipose tissue accumulation ( 131 ). Aging and obesity increased BM adipose tissue, which altered HSC polarization, diminished granulocyte and erythroid differentiation ( 132 ), reduced bone density, and profoundly remodeled the hematopoietic niche by altering expression of extracellular matrix signaling pathways associated with proliferation and differentiation ( 133 ). In this mouse study, a 12-week treadmill regimen delayed high-fat diet–induced obesity, increased trabecular bone mass, and improved the BM microenvironment by partially inhibiting adipokine signaling ( 131 ).…”
Section: Diet and Exercise: Whither The Lotus-eaters?mentioning
confidence: 99%
“…Reduced bone mineral density of older mice diminishes MSC proliferation and response to osteogenic growth factors ( 139 ), resulting in decreased niche factors such as Netrin 1 ( 140 ) and POT1A ( 141 ), leading in turn to DDR defects, BM ROS, and adipose tissue accumulation ( 141 ), which can alter HSC polarization, differentiation ( 132 ), and long-term function ( 133 ). Furthermore, aging increases central marrow LepR + MSC, which, in addition to having a deleterious effect on the sinusoidal vasculature, is associated with decreased osteoprogenitor function ( 142 ).…”
Section: Aging: the End Or Beginning Of The Odyssey?mentioning
confidence: 99%